Pig-a gene mutation assay study design: critical assessment of 3- versus 28-day repeat-dose treatment schedules. (1st July 2020) - Elhajouji, Azeddine; Hove, Tamsanqa Tafara; O'Connell, Oliver; Martus, Hansjoerg; Dertinger, Stephen D
Abstract: The in vivo Pig-a assay is being used in safety studies to evaluate the potential of chemicals to induce somatic cell gene mutations. Ongoing work is aimed at developing an Organisation for Economic Cooperation and Development (OECD) test guideline to support routine use for regulatory purposes (OECD project number 4.93). Among the details that will need to be articulated in an eventual guideline are recommended treatment and harvest schedules. With this in mind, experiments reported herein were performed with Wistar Han rats exposed to aristolochic acid I (AA), 1, 3-propane sultone, chlorambucil, thiotepa or melphalan using each of two commonly used treatment schedules: 3 or 28 consecutive days. In the case of the 3-day studies, blood was collected for Pig-a analysis on days 15 or 16 and 29 or 30. For the 28-day studies blood was collected on day 29 or 30. The effect of treatment on mutant reticulocytes and mutant erythrocytes was evaluated with parametric pair-wise tests. While each of the five mutagens increased mutant phenotype cell frequencies irrespective of study design, statistical significance was consistently achieved at lower dose levels when the 28-day format was used (e.g. 2.75 vs 20 mg/kg/bw for AA). To more thoroughly investigate the dose–response relationships, benchmark dose (BMD) analyses were performed with PROAST software. These results corroborate the pair-wise testing results in that lower BMD values were obtained with the 28-day design. Finally, mutagenic potency, as measured by BMD analyses, most consistently correlated with the mutagens' tumorigenic dose 50 values when the lengthier treatment schedule was used. Collectively, these results suggest that both 3- and 28-day treatment schedules have merit in hazard identification-type studies. That being said, for the purpose of regulatory safety assessments, there are clear advantages to study designs that utilise protracted exposures.